THE MECHANISM OF THE HEALING EFFECT OF PHYSICAL EXERCISES ON THE CARDIOVASCULAR SYSTEM - Jurakulova Diyora Todjiddinovna; Shodikulova Shakhrizoda Mirshukhratovna; Abduakhatov Abdulaziz Abduazizovich; Bakhranov Davronbek Bakhodurovich (Web of Journals Publishing, 2024)
Exercise and sports are of great importance in strengthening the health of young people in our country, increasing the level of physical fitness and maturing their ability to work. Exercise and sports are considered the main tools in the comprehensive physical development of people.
Keywords: Physical culture, healthy personality, maturity, personality health.